Algebra 2 Section 9.1 - PowerPoint PPT Presentation

Ava
slide1 l.
Skip this Video
Loading SlideShow in 5 Seconds..
Algebra 2 Section 9.1 PowerPoint Presentation
Download Presentation
Algebra 2 Section 9.1

play fullscreen
1 / 8
Download Presentation
Algebra 2 Section 9.1
359 Views
Download Presentation

Algebra 2 Section 9.1

- - - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

  1. Algebra 2 Section 9.1 Coordinate Plane y-axis x-axis origin

  2. Graph the points on the coordinate plane. y A. (3,2) B. (-6,5) B C. (0,4) C F A D. (10,-2) x E. (-5,-5) F. (10,4) D E

  3. Give the coordinates of each of the labeled points. y E A. B. C. D. E. F. (-6,1) (-10,-10) (0,0) (0,-6) (1,10) (8,3) F A x C D B.

  4. Graph the equation. - make a chart with x on the left, y on the right - substitute –1,0,1 in for x and then solve for y {-1,0,1} because that keeps the graph near the origin 1. y = 3x - 2 If x = -1 y = 3(-1) – 2 y = -3 – 2 y = -5 y x y -1 0 1 -5 -2 If x = 0 y = 3(0) – 2 y = 0 – 2 y = -2 1 x If x = 1 y = 3(1) – 2 y = 3 – 2 y = 1

  5. Graph the equation. - make a chart with x on the left, y on the right - substitute –1,0,1 in for x and then solve for y {-1,0,1} because that keeps the graph near the origin 2. y = -2x + 4 If x = -1 y = -2(-1) + 4 y = 2 + 4 y = 6 y x y -1 0 1 6 4 If x = 0 y = -2(0) + 4 y = 0 + 4 y = 4 2 x If x = 1 y = -2(1) + 4 y = -2 + 4 y = 2

  6. Graph the equation. - make a chart with x on the left, y on the right 3. y – x = 8 +x +x y = x + 8 - substitute –1,0,1 in for x and then solve for y {-1,0,1} because that keeps the graph near the origin y x y If x = -1 y = -1 + 8 y = 7 -1 0 1 7 8 If x = 0 y = 0 + 8 y = 8 9 x If x = 1 y = 1 + 8 y = 9

  7. Graph the equation. - make a chart with x on the left, y on the right 4. y = -3x - 3 - substitute –1,0,1 in for x and then solve for y {-1,0,1} because that keeps the graph near the origin If x = -1 y = -3(-1) – 3 y = 3 – 3 y = 0 y x y -1 0 1 0 If x = 0 y = -3(0) – 3 y = 0 – 3 y = -3 -3 -6 x If x = 1 y = -3(1) – 3 y = -3 – 3 y = -6